Satisfação da lei de acesso à informação através do sistema de compras eletrônicas do governo do estado do Rio de Janeiro: a transparência proporcionada pelo Sistema Integrado de Gestão de Aquisições – SIGA - Soares, Monique Simões (2015)
This paper analyzes in what proportion the criteria inserted in law 12.527111, known as the Law of Information Access, are attended by the Integrated System of Management Acquisition- SIGA in the state o f Rio de Janeiro. This research is based on item IV of article 8 of the aforementioned law, which determines the compulsory disclosure of the expense records, together with bidding procedures and the contracts, aimed specifically to providing transparency of public spending. The undertaking of public purchases on the internet is an implementation of electronic governance, a most advanced political dimension of the electronic government that provides a number of advantages such as speed in the bidding process. Moreover, dealings effected over a system are easily tracked by audits. Information registered in a single environment ensures the integrated fulfillment of rulesand decreases errors. Electronic bidding is currently, the most widely used modality by Public Administration since it meets demands for more transparency in public acts. The transparency required by society, the changes in legislation, and the technological evolution mal(e the analysis presented in tbis study recommended. In this context, stands out the relevance o f the electronic procurement website analysis of Rio de Janeiro State, the Integrated System of Management Acquisition - SIGA. In arder to create a parameter between SIGA and the systems used by other states, information available in tradings that happened during the year o f 2014 were analyzed. This broad research was made in arder to distinguish the Integrated System of Management Acquisition - SIGA, of Rio de Janeiro State, creating a scale of transparency. In this scale, our website was in fourth place, tied with the state of Amazonas, staying behind São Paulo, Rio Grande do Sul, and Mato Grosso. The qualitative methodology favored an evaluative reading of the use of SIGA, in pursuit of meeting a public policy of significant social impact by the sclccted modality due to rapid results and the participative opening to citizenship surveillance. The intervicws stressed this characteristic inherent to the qualitative posture of the study, with perceptions and timely information. The final considerations highlight advances and limitations in the existing govermnental system of electronic bidding. Nevertheless SIGA, although consolidated and in use since 2009 for ali state authorities of Rio de Janeiro, still needs improvements that will be embedded during 2015,when further research will follow up on new developments.